A study of the satisfaction of the population of major Lithuanian cities with public transport services - Samašonok, Kristina; Jarašūnienė, Aldona; Išoraitė, Margarita (Business: Theory and Practice, 2021)
The article analyzes an evaluation of consumer satisfaction with public transport services in the light of academic literature which highlights the importance of the public transport system and the features of public transport services. The article presents the most influential aspects of public transport services to consumer satisfaction, as evaluated by the residents of major Lithuanian cities. The opportunities for service quality improvements are also presented. In order to examine the elements of consumer satisfaction with public transport services in the major Lithuanian cities, a quantitative analysis was performed and the method of statistical analysis was applied. Student’s test was used to compare and analyze the evaluations by the residents of Vilnius and the residents of other major Lithuanian cities. The most influential elements to satisfaction with public transport services and the overall level of satisfaction with public transport services to the residents of major Lithuanian cities (N = 466) were determined. The research results and insights can be applied in planning the improvements of public transport services.